Otimização dos processos de adsorção e dessorção da octaetilporfirina de níquel em adsorventes à base de carbono - Caetano, Gabriela Costa (2021)
Petroporphyrins are aromatic and nitrogenous macrocycles, of organic origin, which occur naturally in oil and also in sedimentary rocks. In addition to being important biomarker parameters, they have several applications, such as in catalysis and photodynamic therapy. However, they cause damage to the catalytic stages in oil refining. Therefore, due to the importance of removing these compounds from their original fraction, adsorption has been proposed as an alternative process to the commonly used extractive and chromatographic methods. Considering the adsorption and desorption processes of nickel octaethylporphyrin (Ni-OEP), the selection of adsorbents (activated carbon, graphite and partially oxidized graphite) and the optimization of the process operating conditions (solvent, temperature and solid/liquid ratio) were performed. In response, the variables for evaluating the adsorption, adsorption capacity (qe), and desorption, desorption percentage (%desorption) processes were maximized through qualitative and quantitative experimental designs. The kinetics, equilibrium and adsorption thermodynamics studies were carried out; and the adsorbent regeneration cycles were evaluated. As validation of the optimized conditions, qe and %desorption were obtained close to 7.12 mg.g-1 and 37.68%, respectively. As for the adsorption kinetics, the model that best fitted the experimental data was the Elovich equation, in which the equilibrium was reached between 540 and 600 min, with qe = 6.83 mg.g-1; while the equilibrium data were better adjusted by the Freundlich model. The obtained thermodynamic parameters suggest that, under the considered conditions, the adsorption process is spontaneous (ΔG0ads < 0) and exothermic (ΔH0ads < 0). An extraction process was also carried out on the bituminous shales, taken from the Irati Formation, and the presence of nickel octaethylporphyrin was found in the extract. The adsorption and desorption processes of Ni-OEP in the real system had behavior similar to those developed in the model system, with approximately 50% efficiency in petroporphyrin separation. The results obtained allowed to infer that the adsorptive mechanism can be based on the formation of acid-base and π-π interactions between the Ni-OEP molecules and the heterogeneous surface of the coconut shell activated charcoal (CAD), with characteristics of chemical and physical adsorption, respectively.